Reversible binding of divalent cations to Ductin protein assemblies—A putative new regulatory mechanism of membrane traffic processes - Sebők-Nagy, Krisztina; Blastyák, András; Juhász, Gábor; Páli, Tibor (Frontiers in Molecular Biosciences, 2023)
Ductins are a family of homologous and structurally similar membrane proteins with 2 or 4 trans-membrane alpha-helices. The active forms of the Ductins are membranous ring- or star-shaped oligomeric assemblies and they provide various pore, channel, gap-junction functions, assist in membrane fusion processes and also serve as the rotor c-ring domain of V- and F-ATPases. All functions of the Ductins have been reported to be sensitive to the presence of certain divalent metal cations (Me2+), most frequently Cu2+ or Ca2+ ions, for most of the better known members of the family, and the mechanism of this effect is not yet known. Given that we have earlier found a prominent Me2+ binding site in a well-characterised Ductin protein, we hypothesise that certain divalent cations can structurally modulate the various functions of Ductin assemblies via affecting their stability by reversible non-covalent binding to them. A fine control of the stability of the assembly ranging from separated monomers through a loosely/weakly to tightly/strongly assembled ring might render precise regulation of Ductin functions possible. The putative role of direct binding of Me2+ to the c-ring subunit of active ATP hydrolase in autophagy and the mechanism of Ca2+-dependent formation of the mitochondrial permeability transition pore are also discussed.